Enric Ruiz-Geli.Cloud 9 : Cloud 666 tree - Project-New Head Office for the Mies van der Rohe Foundation (1999)
Fundación de Mies van der Rohe, edificio principal en Barcelona, España 1998
Keywords: ESPAÑA; BARCELONA; CLOUD 9; RUIZ-GELI, ENRIC; ARQUITECTURA; PROYECTOS; MIES VAN DER ROHE, LUDWIG; CENTROS CULTURALES